2020
DOI: 10.1186/s12882-020-01919-1
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene polymorphisms and susceptibility to urolithiasis: a meta-regression and meta-analysis

Abstract: Background The currently available data with respect to the association between vitamin D receptor ( VDR ) gene polymorphism and risk to urolithiasis are inconclusive and inconsistent. Hence, an exhaustive meta-analysis can solve the discrepancies and provide a hint for upcoming investigations. Herein, a meta-analysis was carried out to attain a conclusive estimate of the association between VDR gene single nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…Our results revealed a significant association in the overall pooled meta-analysis (OR:1.20; 95% CI: 1.06–1.36). In subgroup analysis, rs2228570 (FokI) showed a significant relationship (OR = 1.28; 95% CI:1.01–1.62) with urolithiasis ( Imani et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed a significant association in the overall pooled meta-analysis (OR:1.20; 95% CI: 1.06–1.36). In subgroup analysis, rs2228570 (FokI) showed a significant relationship (OR = 1.28; 95% CI:1.01–1.62) with urolithiasis ( Imani et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although all this research had shown TaqI polymorphism to be closely related to Asians, a recent meta-analysis opposed the previous claims and reported no association between TaqI, ApaI , and BsmI with urolithiasis in the Asian population [ 21 ]. Another recent meta-analysis claimed with mixed results regarding these SNPs association with Asians and Caucasians population [ 22 ]. Unfortunately, our study is unable to conclude the involvement between VDR gene polymorphism and urolithiasis recurrence in either the Asian or Caucasian population as the population obtained for our VDR gene polymorphism analysis study is largely derived from European countries.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies analyzed the associations of VDR gene expression with urolithiasis risk in different ethnic groups [ 24 ]. A meta-analysis by Imani D et al indicated that although their study did not emphasize the relationship of FokI, TaqI, BsmI, and ApaI in the general sampled examination, but it proposes that ApaI and TaqI SNPs are linked to the bigger risk of urolithiasis in East-Asian and Caucasians populations [ 5 ]. It was indicated that urinary calcium excretion has increased in response to vitamin D (VitD) supplements, at least in some groups of kidney stone formers.…”
Section: Discussionmentioning
confidence: 99%
“…Some genes are the most highlighted ones in recurrent kidney stones, like Vitamin D Receptors (VitD R), Claudin 14 (CLDN14), and Calcium-sensing receptor (CaSR) [ 5 , 6 ]. Despite the established importance of these three genes in kidney stone formation, their promoter methylations have not evaluated yet.…”
Section: Introductionmentioning
confidence: 99%